Short report on the rescue excavations in the Roman Age Barbaricum near Abony (Pest County, Hungary) - Simon, Bence; Joháczi, Szilvia (Dissertationes Archaeologicae, 2019)
The staff of the Institute of Archaeological Sciences of Eötvös Loránd University unearthed a Sarmatian settlement and a cemetery near Abony (Pest County, Hungary) in the autumn of 2018. The preliminary results point to the area’s economic importance around the turn of the 2nd–3rd century AD.